Uji Aktivitas Antiinflamasi Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa bilimbi L.) Terhadap Penghambatan Denaturasi Protein - Dheani Sepalia Novika; Riska Ahsanunnisa; Dwi Fitri Yani (Stannum : Jurnal Sains dan Terapan Kimia, 2021)
Inflammation is a cell breakdown caused by bacteria, chemical substances, mechanical trauma and physical trauma. Testing of such anti-inflammatory activity can be done in-vitro with the method of protein denaturation using natural materials starfruit leaf (Averrhoa Oxalidaceae L.). This research aims to determine the comparison of the activity of ethanol extract in the strafruit leaf and sodium diclofenac. strafruit Leaf Ethanol extract is made with a concentration of 1 ppm, 10 ppm and 100 ppm with the comparator of sodium diclofenac. Antiinflammatory resistance is obtained by calculating the percentage of inhibition of protein denaturation. The result of a test of strafruit leaf ethanol extract (Averrhoa Oxalidaceae L.) with a value of IC50 of 20.20 μg/mL indicates an inhibitory percentage of more than 20% at the lowest concentration of 1 ppm, while IC50 sodium diclofenac of 14.93 μg/mL with an inhibitory percentage of more than 20% at 5 ppm .